Crystal structures of X‐phase in the Sb–Te binary alloy system. Issue 11 (31st October 2013) - Kifune, K.; Fujita, T.; Tachizawa, T.; Kubota, Y.; Yamada, N.; Matsunaga, T.
<x xml:space="preserve">Abstract</x> The crystallisation of 5 different Sb–Te alloy films with various compositions deposited by DC sputtering was examined using X‐ray powder diffraction and four‐dimensional superspace analysis. The as‐sputtered films had either amorphous or fairly simple crystal structures. However, when the films were heated, the modulation period γ was found to change significantly and continuously for all specimens and they eventually settle in specific homologous structures. These structures and the composition dependence were revealed. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>